High incidence of childhood pneumonia at high altitudes in Pakistan: a longitudinal cohort study - Aamir J Khan; Hamidah Hussain; Saad B Omer; Sajida Chaudry; Sajid Ali; Adil Khan; Zayed Yasin; J Khan Imran; Rozina Mistry; Imam Yar Baig; Franklin White; Lawrence H Moulton; et al. (The World Health Organization, 2009)
OBJECTIVE:To determine the incidence of pneumonia and severe pneumonia among children living at high altitudes in Pakistan. METHODS: A longitudinal cohort study was conducted in which 99 female government health workers in Punial and Ishkoman valleys (Ghizer district, Northern Areas of Pakistan) enrolled children at home, conducted home visits every 2 weeks and actively referred sick children to 15 health centres. Health centre staff used Integrated Management of Childhood Illness criteria to screen all sick children aged 2-35 months and identify those with pneumonia or severe pneumonia. FINDINGS: Community health workers enrolled 5204 eligible children at home and followed them over a 14-month period, ending on 31 December 2002. Health centre staff identified 1397 cases of pneumonia and 377 of severe pneumonia in enrolled children aged 2-35 months. Among children reported with pneumonia, 28% had multiple episodes. Incidence rates per 100 child-years of observation were 29.9 for pneumonia and 8.1 for severe pneumonia. Factors associated with a high incidence of pneumonia were younger age, male gender and living at high altitude. CONCLUSION: Pneumonia incidence rates in the Northern Areas of Pakistan are much higher than rates reported at lower altitudes in the country and are similar to those in high-altitude settings in other developing countries. More studies are needed to determine the causes of pneumonia in these high-mountain communities. However, early introduction of the vaccines that are known to prevent pneumonia should be considered.